Micro-scale computational modeling of graphene-based nanocomposites – Influence of filler-matrix interface failure. (November 2020) - Sadeghpour, Ebrahim; Guo, Yangbo; Chua, Daniel; Shim, Victor P.W.
Abstract: The effect of failure at the filler-matrix interface on the tensile stress-strain response of graphene-based polymer nanocomposites is studied using micro-scale finite element (FE) modeling. Interfacial failure can occur in the form of debonding or slip. Based on previous studies (Jiang et al., 2014 ; Anagnostopoulos et al., 2015 ; Li et al., 2017 ), interfacial slip, which causes friction-like interaction between the filler and matrix, is identified as the major failure mechanism that affects the nanocomposite response. By establishing single-filler models in ABAQUS, it is demonstrated that interfacial slip affects the stress-strain response of the nanocomposite in two ways. Firstly, it limits the load that can be transferred to the filler. Secondly, it causes a shear displacement discontinuity across the interface, and this generates additional strain over and above those of the matrix and filler; this reduces the level of stress enhancement in the nanocomposite that the incorporation of fillers contribute, and under certain conditions, even weaken the nanocomposite. Models with fully aligned and randomly oriented fillers are also established to examine the influence of parameters such as filler orientation, interfacial slip strength, and filler aspect ratio, on the tensile response of the nanocomposite. The model developed is employed to describe the tensile response of an actual polyvinyl alcohol (PVA)- graphene oxide (GO) nanocomposite, and good correlation with experiments is observed. Highlights: Study of uniaxial tensile stress-strain response of graphene-based polymer nanocomposites through establishment of FE RVE models with fully aligned and randomly oriented fillers Identification of friction-like slip between the matrix and the fillers as the dominant interfacial failure mechanism, resulting in a significant effect on the stress-bearing capacity of the nanocomposite Examination of how interfacial slip limits the stress transferred to the filler and generates additional strain which would be absent with perfect bonding Verification of the FE model by data from experimental tests on a PVA-graphene oxide nanocomposite